Attorney General John Van de Kamp Keynotes Fresno County Bar Association Law Day Luncheon - Watkins, Howard::::::::: (1983)
John Van de Kamp seated at press conference; microphones from KFRE 940, 30, 47, 26, KYNO, KMAX Tape recorder and power supply on table